The Effect of Customer Experience, Customer Satisfaction and Brand Image on Customer Loyalty in Shopping Centers in The City of Solo - Erni Widiastuti; Sukesi Sukesi; Asih Handayani (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine the effect of customer experience, customer satisfaction and brand image on customer loyalty in shopping centers in the city of Solo. Where the shopping center is a company that carries the concept of one stop shopping, namely Solo Grand Mall, Solo Square and Solo Paragon. The population of this study were visitors to Solo Grand Mall, Solo Square and Solo Paragon where the number could not be counted exactly so using the Cochran calculation basis, it could be seen that the number of respondents was 385 respondents with ages greater than or equal to 18 years, and had shopped in one month final. The sample was selected by non-probability sampling method. The results of the study show that customer experience, customer satisfaction and brand image have a significant effect on customer loyalty at shopping centers in the city of Solo.